The Implementation of Machine Learning on MSMEs Product Sales in Indonesia: A Systematic Literature Review - Lantana, Dhieka Avrilia; Digdowiseiso , Kumba (CV ODIS, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are crucial in Indonesia. They contribute significantly to employment absorption and can be initiated with minimal capital. However, this does not imply that MSMEs are without potential challenges. They often face difficulties in capturing markets and implementing professional management practices. This is why technological assistance is needed within this sector. One anticipated technical aid is the application of Machine Learning as a marketing tool. This aligns with the characteristics of Machine Learning, which has long been instrumental in various businesses. This research employs the systematic literature review method to explore how Machine Learning can help MSMEs. Findings based on the SLR demonstrate that Machine Learning not only aids in marketing but also enhances operational efficiency.